2019
DOI: 10.32598/ajnpp.5.1.3
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Artificial Intelligence Applications and Psychology

Abstract: Psychotherapy endows a sense of control in patients gripped with emotional conflicts; it allows them to handle their reflexes and regain composure through conscious and behavioral alterations. These transformational changes can be brought about by improving their listening skills, observational capacities, creating awareness, and making them more attentive and intervening. Conventional psychotherapy calls for one-to-one sessions during treatment. Considering the increased access to Information Technology (IT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Ten of the 27 excluded studies either tried to predict the outcome of cognitive behavior therapy by using natural language processing, or tried to predict optimal therapeutic interventions with sociodemographic data (30-40). Another 16 studies excluded were reviews about machine learning and its utilization within psychotherapy, psychopharmacotherapy, and diagnostics (19,27,38,(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51). Another 8 Studies were excluded because they treated patients with psychotherapy, yet did not specify which kind of treatment approach they used (22, 29, 52-57).…”
Section: Study Selectionmentioning
confidence: 99%
“…Ten of the 27 excluded studies either tried to predict the outcome of cognitive behavior therapy by using natural language processing, or tried to predict optimal therapeutic interventions with sociodemographic data (30-40). Another 16 studies excluded were reviews about machine learning and its utilization within psychotherapy, psychopharmacotherapy, and diagnostics (19,27,38,(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51). Another 8 Studies were excluded because they treated patients with psychotherapy, yet did not specify which kind of treatment approach they used (22, 29, 52-57).…”
Section: Study Selectionmentioning
confidence: 99%
“…The literature on artificial intelligence supports that there are several applications of specialized tools and techniques that could be employed to enhance psychotherapy [19].…”
Section: Artificial Intelligence In the Field Of Psychotherapymentioning
confidence: 99%
“…However, human behaviour itself cannot be copied in totality by technology. 10 A similar review in Canada, that addressed implementation of AI in healthcare, showed that machines do not replace healthcare providers since it is not about making better decisions, rather about collecting and having better information. Therefore, maximising the healthcare benefits can be through reaching the maximum potential of combining both the human and AI technology.…”
Section: How Has Artificial Intelligence Contributed To Healthcare Provision Benefits?mentioning
confidence: 99%